Activatable near infrared dye conjugated hyaluronic acid based nanoparticles as a targeted theranostic agent for enhanced fluorescence/CT/photoacoustic imaging guided photothermal therapy. (July 2017) - Liang, Xiaolong; Fang, Lei; Li, Xiaoda; Zhang, Xu; Wang, Fan
Abstract: Targeted theranostic nano-system integrating functions of both diagnosis and therapy shows great potential for improving diagnosis and therapeutic efficacy. Herein, multifunctional nanoparticle based on activatable hyaluronic acid (HA) conjugating two near-infrared (NIR) dyes of Cy5.5 and IR825 was successfully designed and fabricated, and simultaneously used as a carrier for encapsulating perfluorooctylbromide (PFOB). In this system, PFOB showed good capability to absorb the X-rays, Cy5.5 on the outer surface acted as a fluorescent dye activatable by hyaluronidases (Hyals) in the tumor, and IR825 in the core as a photothermal agent. The obtained nanoparticles (NPs) of PFOB@IR825-HA-Cy5.5 can be utilized for triple X-ray computed tomography (CT), fluorescence and photoacoustic imaging. When PFOB@IR825-HA-Cy5.5 NPs were intravenously injected into the mice bearing HT-29 tumor, efficient tumor accumulation was clearly observed, as revealed by the triple modal imaging. An in vivo tumor treatment experiment was conducted by combination of PFOB@IR825-HA-Cy5.5 and near-infrared laser irradiation, achieving effective tumor ablation in mice. Therefore, PFOB@IR825-HA-Cy5.5 NPs is a safe, efficient, imageable photothermal nanoprobe, showing great potential for cancer theranostics. Graphical abstract: Theranostic agent of PFOB@IR825-HA-Cy5.5 NPs was successfully fabricated. PFOB showed good capability to absorb the X-rays, Cy5.5 on the outer surface acted as fluorescent probe, while IR825 in the core as photothermal agent. By utilizing the fluorescence quench effect of the two dyes and degradability of HA by hyaluronidase (Hyal-1) in the tumor, strong fluorescence enhancement could be achieved to delineate the tumor more clearly. Such theranostic agent demonstrated excellent diagnostics capability without compromising the photothermal therapy efficacy, and can be utilized as an active targeting agent for triple X-ray computed tomography (CT), photoacoustic and activatable fluorescence imaging guided photothermal ablation of tumors.